Differential Effects of Three Techniques for Hepatic Vascular Exclusion during Resection for Liver Cirrhosis on Hepatic Ischemia-Reperfusion Injury in Rats - Changjun Jia; Chaoliu Dai; Hailiang Wang; Yi Wan; Yunyu Qiao; Feng Xu; Songlin Peng; Yang Zhao; Chuang Zhao; Liang Zhao (Gastroenterology Research and Practice)
Background/Aims. Hepatic ischemia-reperfusion (I/R) injury is a serious concern during hepatic vascular occlusion. The objectives of this study were to assess effects of three techniques for hepatic vascular occlusion on I/R injury and to explore the underlying mechanisms. Methods. Liver cirrhotic rats had undertaken Pringle maneuver (PR), hemihepatic vascular occlusion (HH), or hepatic blood inflow occlusion without hemihepatic artery control (WH). Levels of tumor necrosis factor alpha (TNF-α), nuclear factor kappa B (NF-κB), toll-like receptor 4 (TLR4), TIR-domain-containing adapter-inducing interferon-β (TRIF), and hemeoxygenase 1 (HMOX1) were assayed. Results. The histopathologic analysis displayed that liver harm was more prominent in the PR group, but similar in the HH and WH groups. The HH and WH groups responded to hepatic I/R inflammation similarly but better than the PR group. Mechanical studies suggested that TNF-α/NF-κB signaling and TLR4/TRIF transduction pathways were associated with the differential effects. In addition, the HH and WH groups had significantly higher levels of hepatic HMOX1 (P<0.05) than the PR group. Conclusions. HH and WH confer better preservation of liver function and protection than the Pringle maneuver in combating I/R injury. Upregulation of HMOX1 may lead to better protection and clinical outcomes after liver resection.